Cafestol Inhibits High-Glucose-Induced Cardiac Fibrosis in Cardiac Fibroblasts and Type 1-Like Diabetic Rats. (31st December 2020) - Liu, Ju-Chi; Chen, Po-Yuan; Hao, Wen-Rui; Liu, Yi-Chung; Lyu, Ping-Chiang; Hong, Hong-Jye
Abstract : Diabetes is associated with the development of myocardial fibrosis, which is related to various cardiac diseases. Cafestol, one of the active ingredients in coffee, has been reported to exert biological effects. However, whether cafestol can ameliorate diabetes-induced cardiac fibrosis remains unknown. The aim of this study was to evaluate the effects of cafestol on cardiac fibrosis in high-glucose-treated cardiac fibroblasts and streptozocin- (STZ-) induced diabetic rats. Rat cardiac fibroblasts were cultured in high-glucose (25 mM) media in the absence or presence of cafestol, and the changes in collagen synthesis, transforming growth factor- β 1 (TGF- β 1) production, and related signaling molecules were assessed on the basis of 3 H-proline incorporation, enzyme-linked immunosorbent assay, and western blotting. Cardiac fibroblasts exposed to high-glucose conditions exhibited increased collagen synthesis, TGF- β 1 production, and Smad2/3 phosphorylation, and these effects were mitigated by cafestol treatment. Furthermore, cafestol increased the translocation of nuclear factor erythroid 2-related factor 2 and increased the expression of heme oxygenase-1. The results of molecular docking analysis suggested a selective interaction of cafestol with Kelch-like ECH-associated protein 1. The rats with untreated STZ-induced diabetes exhibited considerable collagen accumulation, which was ameliorated by cafestol. Moreover, activities of catalase, superoxide dismutase, general matrix metalloproteinase, and reduced glutathione concentration were upregulated, whereas malondialdehyde level was downregulated by treatment with cafestol in rats with cardiac fibrosis. These findings highlight the effects of cafestol, which may be useful in treating diabetes-related cardiac fibrosis.